Unusual Site of Metastasis of Bronchogenic Carcinoma - Pant, P; Sedhain, A; D'Souza, S; Renuka, B G (Kathmandu University Medical Journal, 2012)
Metastasis of bronchogenic carcinoma to the chest wall and axillary lymphnodes is a rare occurence. This study reports the case of a patient presenting with chest wall swelling as initial symptom which on evaluation was found to be a lymphnode metastasis. The patient also had axillary lymphnode metastasis on the same side as the chest swelling with a contralateral pleural effusion. Here, we discuss the pathways and possible mechanisms of contra lateral auxillary and chest wall lymphnode involvement without ispilateral nodal involvement in bronchogenic carcinoma. http://dx.doi.org/10.3126/kumj.v8i4.6243 Kathmandu Univ Med J 2010;8(4):420-22